Natural Flavonoids Targeting Deregulated Cell Cycle Progression in Cancer Cells - Singh, Rana P.; Agarwal, Rajesh (Current Drug Targets, 2006)
The prolonged duration requiring alteration of multi-genetic and epigenetic molecular events for cancer development provides a strong rationale for cancer prevention, which is developing as a potential strategy to arrest or reverse carcinogenic changes before the appearance of the malignant disease. Cell cycle progression is an important biological event having controlled regulation in normal cells, which almost universally becomes aberrant or deregulated in transformed and neoplastic cells. In this regard, targeting deregulated cell cycle progression and its modulation by various natural and synthetic agents are gaining widespread attention in recent years to control the unchecked growth and proliferation in cancer cells. Infact, a vast number of experimental studies convincingly show that many phytochemicals halt uncontrolled cell cycle progression in cancer cells. Among these phytochemicals, natural flavonoids have been identified as a one of the major classes of natural anticancer agents exerting antineoplastic activity via cell cycle arrest as a major mechanism in various types of cancer cells. This review is focused at the modulatory effects of natural flavonoids on cell cycle regulators including cyclin-dependent kinases and their inhibitors, cyclins, p53, retinoblastoma family of proteins, E2Fs, check-point kinases, ATM/ATR and survivin controlling G1/S and G2/M check-point transitions in cell cycle progression, and discusses how these molecular changes could contribute to the antineoplastic effects of natural flavonoids.
Keywords: ATM/ATR